Perencanaan Pengembangan Aksesibilitas Jalan di Kecamatan Selat - Aldi Saputra; Dandi Achmad Risadi; Fonni Inda; Jelita Audika; Elysua Nertado Krisopras; Muhammad Zikri Ramadhan; Zaidan Rahmani; Sutan Parasian Silitonga (Fakultas Teknik Universitas Palangka Raya, 2025)
The Engineering for Building and Impact (TMB) Program is one of the programs of the Faculty of Engineering, Palangka Raya University, which is present as a forum for community service that integrates academic activities, research, and direct implementation in the field. This program is designed to assist village or sub-district governments in preparing development master plans, planning infrastructure, and preparing technical documents such as Budget Plans (RAB) and regional maps. Selat District, Kapuas Regency, Central Kalimantan Province is an area with quite high social and economic activities so that it requires decent and optimally functioning road infrastructure. However, on several road sections, damage is still found such as random cracks, crocodile cracks, longitudinal cracks, and damaged patches. This study aims to develop a technical plan for developing road accessibility by identifying existing conditions and planning appropriate road maintenance. The research methods used included field surveys, visual observation of road pavement conditions, primary and secondary data collection, and analysis of the type and extent of road damage. The results indicate that recommended maintenance measures include routine and periodic repairs on several road segments on Jalan Kalimantan, Selat District. This plan is expected to serve as a reference for improving road quality, comfort, and safety for road users, while supporting sustainable regional development.